The Creation and the use of Profiles of Banks for Genetic Prosecution Purposes Criminal in Brazil : An Analysis Through Bioethics and by the Advent of Law 12,654 / 2012 - Carlos Eduardo Martins Lima (Revista de Biodireito e Direito dos Animais, 2015)
This article aims to explain in general terms, the analysis of the use of banks of genetic profiles for criminal prosecution purposes in Brazil through the advent of Law 12,654 / 2012 and through the principles of bioethics , international documents, principles and guarantees constitutional and human rights , seeking to emphasize the importance of using this forensic tool and technology to fight crime in Brazil. Moreover, through critical reflection , we seek to analyze the legal instrument focusing on the Brazilian criminal law and forensic genetics , through the study of human identification. At the end , we seek a conclusion on the effectiveness of this technology in the criminal context